2022
DOI: 10.3389/fimmu.2022.1013498
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric and visualization analysis of macrophages associated with osteoarthritis from 1991 to 2021

Abstract: BackgroundMacrophages significantly contributes to symptomology and structural progression of osteoarthritis (OA) and raise increasing attention in the relative research field. Recent studies have shown that tremendous progress has been made in the research of macrophages associated with osteoarthritis. However, a comprehensive bibliometric analysis is lacking in this research field. This study aimed to introduce the research status as well as hotspots and explore the field of macrophages research in OA from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…The number of articles that had the key word of OA in their title generated by the EU, Non-EU and Geo-EU Countries increased from the year of 2007 to 2021. Our findings were in line with previous studies that analyzed the trend in publications previously (Zhang et al, 2022;Yang et al, 2022;Hu et al, 2022;Patel et al, 2022;Muthu et al, 2022;Molyneux et al, 2022;Ren et al, 2021;Li et al, 2021;Zhang et al, 2020;Liu et al, 2020;Li et al, 2020 R;Chen et al, 2021;Xing et al, 2018;Gupta & Gupta, 2018;Gao et al, 2020).Furthermore, we focused on comparing the impact of OA research from Europe by analyzing trends from the years of 2007 to 2021 for articles published in the EU, non-EU associated and geographically European countries. We limited our search to articles only and did not include all documents.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The number of articles that had the key word of OA in their title generated by the EU, Non-EU and Geo-EU Countries increased from the year of 2007 to 2021. Our findings were in line with previous studies that analyzed the trend in publications previously (Zhang et al, 2022;Yang et al, 2022;Hu et al, 2022;Patel et al, 2022;Muthu et al, 2022;Molyneux et al, 2022;Ren et al, 2021;Li et al, 2021;Zhang et al, 2020;Liu et al, 2020;Li et al, 2020 R;Chen et al, 2021;Xing et al, 2018;Gupta & Gupta, 2018;Gao et al, 2020).Furthermore, we focused on comparing the impact of OA research from Europe by analyzing trends from the years of 2007 to 2021 for articles published in the EU, non-EU associated and geographically European countries. We limited our search to articles only and did not include all documents.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings for these parameters were in line with previous studies (Wang K et al, 2019;Chen et al, 2021;Wang et al, 2020;Zhang et al, 2022;Li et al, 2020;Patel et al, 2022). We did not use CiteSpace or VOSviewer software's for bibliometric and visualization analysis (Yang et al, 2022). Instead, we wanted to focus on academic impact of multi-disciplinary and collaborative studies.…”
Section: Discussionmentioning
confidence: 99%
“…Leung et al reported that concentrations of TNF-α, IL-6, and IL-8 are associated with pain on movement, with only TNF-α being involved in the exacerbation of the pain at rest, which is characteristic of sensitized pain in the synovial fluid of knee OA (KOA) [33]. Further, it is known that these pro-inflammatory cytokines are primarily expressed by synovial monocytes and macrophages in OA joints [34][35][36]. Further, CD14-positive macrophages regulate NGF via pro-inflammatory cytokine production in the synovial membrane of KOA [34][35][36].…”
Section: Molecules Involved In Ps and Cs In Oamentioning
confidence: 99%
“…Further, it is known that these pro-inflammatory cytokines are primarily expressed by synovial monocytes and macrophages in OA joints [34][35][36]. Further, CD14-positive macrophages regulate NGF via pro-inflammatory cytokine production in the synovial membrane of KOA [34][35][36]. Synovial CD163 mRNA expression is positively correlated with pain at rest, while CD163+CD14 low macrophages expressing TNF-α might be a major contributor to hip OA (HOA) pain [34].…”
Section: Molecules Involved In Ps and Cs In Oamentioning
confidence: 99%
“…Hu et al revealed 10 hot microRNAs of chondrocytes in OA and their potential targets based on bibliometrics ( Hu et al, 2022 ). Yang et al (2022) performed a bibliometric analysis of the knowledge structure and trends in OA-related macrophage research. Zhang et al (2022) visualized the historical evolution and future trends of hyaluronic acid for OA.…”
Section: Introductionmentioning
confidence: 99%